Sec-service level agreement analysis of OFB mode in block cipher. (1st January 2014) - Hong, Jinkeun
In a cipher device, the OFB operation mode must be analysed for quality performance according to various secure communication channel environments. Many cipher applications have evaluated issues of security quality. This paper reviews channel transmission performance for OFB operation mode of cipher communication in a fading channel. This result contributes for Sec-SLA evaluation and probabilistic error effect of each cipher device.